Severe Hyperprolactinemia Promotes Brown Adipose Tissue Whitening and Aggravates High Fat Diet Induced Metabolic Imbalance - Lopez-Vicchi, Felicitas; De Winne, Catalina; Ornstein, Ana Maria; Sorianello, Eleonora; Toneatto, Judith; Becu-Villalobos, Damasia (Frontiers in Endocrinology, 2022)
Background: The association of high serum prolactin and increased body weight is positive but controversial, therefore we hypothesized that additional factors such as diets and the impact of prolactin on brown adipose tissue may condition its metabolic effects. Methods: We used LacDrd2KO females with lifelong severe hyperprolactinemia due dopamine-D2 receptor deletion from lactotropes, and slow onset of metabolic disturbances, and compared them to their respective controls (Drd2 loxP/loxP). Food intake, and binge eating was evaluated. We then challenged mice with a High Fat (HFD) or a Control Diet (CD) for 8 weeks, beginning at 3 months of age, when no differences in body weight are found between genotypes. At the end of the protocol brown and white adipose tissues were weighed, and thermogenic and lipogenic markers studied, using real time PCR (Ucp1, Cidea, Pgc1a, Lpl, adiponectin, Prlr) or immunohistochemistry (UCP1). Histochemical analysis of brown adipose tissue, and glucose tolerance tests were performed. Results: Hyperprolactinemic mice had increased food intake and binge eating behavior. Metabolic effects induced by a high fat diet (HFD) were exacerbated in lacDrd2KO mice. Hyperprolactinemia aggravated HFD-induced body weight gain and glucose intolerance. In brown adipose tissue pronounced cellular whitening as well as decreased expression of the thermogenic markers Ucp1 and Pgc1a were observed in response to high prolactin levels, regardless of the diet, and furthermore, hyperprolactinemia potentiated the decrease in Cidea mRNA expression induced by HFD. In subcutaneous white adipose tissue hyperprolactinemia synergistically increased tissue weight, while decreasing Prlr, Adiponectin and Lpl mRNA levels, also regardless of the diet. Conclusions: Pathological hyperprolactinemia has a strong impact in brown adipose tissue, lowering thermogenic markers and evoking tissue whitening. Furthermore, it modifies lipogenic markers in subcutaneous white adipose, and aggravates glucose intolerance and the decrease in thermogenic marker Cidea, induced by HFD. Therefore, severe high prolactin levels may represent an adjuvant player in the development of obesity induced by high fat diets.